The Analisis Implementasi Program Indonesia Sehat dengan Pendekatan Keluarga ( Pis-Pk ) oleh Petugas Kesehatan di Puskesmas Sako - Citra Meiriza; Erma Gustina; Chairil Zaman (HEALTH CARE : JURNAL KESEHATAN, 2022)
The Healthy Indonesia Program with a Family Approach (PIS-PK) is implemented by upholding 3 main pillars, namely the application of a healthy paradigm, strengthening health services, and implementation of the National Health Insurance (JKN). The PIS-PK stage begins with collecting family health data. This study aims to describe the implementation of PIS-PK by health workers at the Sako Health Center in Palembang City in 2022. This study is qualitative research. There were 3 informants in this study. This research was conducted in June 2022. The data was collected using in-depth interviews, then the data were analyzed by the steps of categorizing, and classifying the data obtained from the results of in-depth interviews. The implementation of PIS-PK at the Sako Health Center has been running even though there are obstacles and obstacles. The implementation of PIS-PK at the Sako Health Center is influenced by communication factors, resources, attitudes, and bureaucratic structures. The communication factor is a lack of socialization by related and cross-sectoral agencies. Resource factors including the involvement of human resources, infrastructure in the form of funds, and completeness of data collection are still limited. The attitude factor of the officers is committed and cooperating. Bureaucratic structure factors related to SOP and SK have been made. From the results of this study, it was concluded that the implementation of PIS-PK had been carried out even though there were obstacles. It required cross-sectoral socialization and optimizing the community approach, and maximizing funds to complete facilities and infrastructure.